THE INFLUENCE OF PERSONALITY TYPE AND KNOWLEDGE ON CUSTOMER’S DECISIONS TO SAVE AT BANK MALUKU - Muspiha Muspiha; Nanik Indrayani; Riki Bugis; Susiati Susiati (Jurnal Ekonomi dan Manajemen, 2022)
The purpose of this study was to determine and analyze the influence of personality type and knowledge on customer's decision to save at PT Bank Maluku branch Namlea. Identify independent variables associated with the type of personality and knowledge while the dependent variable is the customer's decision, object of this research is PT Bank Maluku branch Namlea with population The research is customers who have savings deposits and current accounts and the number of samples is 175 customers and the analysis used is multiple linear regression analysis. The results of the study found that the three hypotheses were accepted, meaning that partially personality type had a positive effect on customer decisions, a value of 0.116 knowledge has a positive effect on customer decisions with a value of 0.250 and together personality type and knowledge have a statistical effect on customer decisions with a calculated F value of 2.675. Meaning that personality type and knowledge are significant explanations of customer decisions.